Interventions Addressing Informational Needs of Adults with Primary Malignant Brain Tumors: A Systematic Review - Maria Camilla Mathiasen; Florien Boele; Georgia K B Halkett; Anders Overby Sjøstrøm; Dorte Schou Nørøxe; Helle Pappot; Karin Piil (Neuro-Oncology Practice, 2026)
Abstract Background Patients with primary malignant brain tumors (PMBT) and their caregivers face informational challenges due to cognitive impairment, emotional distress, and complex treatment trajectories. Although informational interventions have been developed, effectiveness and scope remain unclear. This systematic review aimed to synthesise evidence on interventions addressing informational needs in this population. Methods Five databases (MEDLINE, Embase, Cochrane Library, CINAHL, PsycINFO) were searched for studies published between 2015 and 2025. Studies included adult patients with PMBT and evaluated interventions targeting informational needs or understanding. All study designs were included. Data were extracted and synthesised using a narrative approach due to heterogeneity. Methodological quality was assessed using the Mixed-Methods Appraisal Tool. Results Thirty studies were included, comprising qualitative, quantitative, and mixed-methods designs. Interventions were heterogeneous and included psychoeducational, psychological, communication-support, family-based, and digital approaches. Many interventions improved outcomes such as psychological distress, disease understanding, self-management, and quality of life. Communication-support tools enhanced recall and patient involvement, while family-based interventions improved shared understanding. No single intervention was designed to comprehensively address informational needs across the disease trajectory, reflecting the complexity of care needs in PMBT. Information-related outcomes were inconsistently defined and rarely primary endpoints. Methodological limitations included sample sizes, variable adherence, and limited use of validated measures. Conclusions Informational needs in PMBT care are complex, dynamic, and insufficiently addressed by existing interventions. Findings support the need for flexible, tailored, and iterative informational strategies rather than single standardized approaches. Future research should prioritize standardized outcome measures and develop adaptive interventions aligned with evolving patient and caregiver needs.